Tumor-targeted drug delivery and MRI contrast enhancement by chlorotoxin-conjugated iron oxide nanoparticles. (August 2008) - Sun, Conroy; Fang, Chen; Stephen, Zachary; Veiseh, Omid; Hansen, Stacey; Lee, Donghoon; Ellenbogen, Richard G; Olson, Jim; Zhang, Miqin
Aims: This study examines the capabilities of an actively targeting superparamagnetic nanoparticle to specifically deliver therapeutic and MRI contrast agents to cancer cells.Materials & methods: Iron oxide nanoparticles were synthesized and conjugated to both a chemotherapeutic agent, methotrexate, and a targeting ligand, chlorotoxin, through a poly(ethylene glycol) linker. Cytotoxicity of this nanoparticle conjugate was evaluated by Alamar Blue cell viability assays, while tumor-cell specificity was examined in  vitro and in  vivo by MRI.Results & discussion: Characterization of these multifunctional nanoparticles confirms the successful attachment of both drug and targeting ligands. The targeting nanoparticle demonstrated preferential accumulation and increased cytotoxicity in tumor cells. Furthermore, prolonged retention of these nanoparticles was observed within tumors in  vivo .Conclusion: The improved specificity, extended particle retention and increased cytotoxicity toward tumor cells demonstrated by this multifunctional nanoparticle system suggest that it possesses potential for applications in cancer diagnosis and treatment.